The Value of the Frog Lateral View Radiograph for Detecting Collapse of Femur Head Necrosis: A Retrospective Study of 1001 Cases - Yang, Fan; Deng, Xiaoqiang; Xin, Pengfei; Hong, Zhinan; Pang, Fengxiang; He, Wei; Wei, Qiushi; Li, Ziqi (Frontiers in Medicine, 2022)
Aims: The collapse in femur head necrosis is generally detected by CT or MRI which are not primary routine examination at every follow-up in developing countries. The purpose of this study was to verify the reliability of the frog lateral view radiograph in detecting the collapse of femoral head. Methods: We retrospectively included 1001 hips of 620 patients with femur head necrosis. The anteroposterior view and frog lateral view of X-ray standard radiographs, CT and MRI of patients were collected and simultaneously evaluated by three orthopedists to evaluate the condition of collapse according to the unified standard. The inter-observer reliability of each view of X-ray for detecting the collapse were analyzed through the weighted Cohen’s kappa index. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of each evaluation method were also calculated. Results: A moderate or substantial reliability was indicated in the evaluation of frog lateral view radiograph, whereas the anteroposterior view only showed fair or poor reliability. Using the CT or MRI results of collapse as the gold standard, the frog lateral view indicated higher sensitivity and accuracy than the anteroposterior view (sensitivity: 82.8% versus 64.9%; accuracy: 87.1% versus 73.9%). The combination of the anteroposterior view and frog lateral view indicated higher reliability than individual views. Conclusion: The frog lateral view radiograph has higher sensitivity and accuracy than anteroposterior view. It is a complementary method to AP view for detecting the collapse in femur head necrosis during the follow-up, which has moderate or substantial inter-observer reliability.